The private sector's role in agricultural extension systems: Potential and limitations - Feder, Gershon; Birner, Regina; Anderson, Jock R. (Emerald Publishing Limited, 2011)
The poor performance of public agricultural extension systems in developing countries engendered interest in pluralistic concepts of extension involving a variety of service providers. Within the reform agenda, modalities relying on private‐sector providers were perceived as a path to improvement. This paper aims to assess the potential and limitations of such modalities.The paper discusses the conceptual underpinnings of these extension approaches, highlights theoretical and practical challenges inherent in their design, and provides an assessment of several performance‐based case studies described in the formal and informal literature.Many of the modalities reviewed entail partnerships between the public sector, farmers' organizations or communities, and private‐sector providers. The paper concludes that while private‐sector participation can overcome some of the deficiencies of public extension systems, there are also challenges that have been faced, including misuse of public funds, insufficient accountability to farmers, inequitable provision of service, inadequate quality, and limited coverage of the wide range of farmers' needs.The review suggests that private‐sector involvement in extension is no panacea. Extension systems need not be uniform, and will require different providers for different clienteles, with public providers and funding focusing more on smaller‐scale and less commercial farmers. The public sector may need to provide some regulatory oversight of private‐sector extension activities, particularly when public funding is involved.The paper draws conclusions from a diverse range of experiences, some of which are recent, and provides comparative insights. It may be of interest to development scholars and practitioners.